Hydroalcoholic crude extract of Casearia sylvestris Sw. reduces chronic post-ischemic pain by activation of pro-resolving pathways - Piovezan, Anna P.; Batisti, Ana P.; Benevides, Maria L.A.C.S.; Turnes, Bruna L.; Martins, Daniel F.; Kanis, Luiz; Duarte, Elisa C.W.; Cavalheiro, Alberto J. [UNESP]; Bueno, Paula C.P. [UNESP]; Seed, Michael P.; Norling, Lucy V.; Cooper, Dianne; et al. (Elsevier, 2017)
Ethnopharmacological relevance Casearia sylvestris Sw. is widely used in popular medicine to treat conditions associated with pain. Aim of the study The present study investigated the influence of hydroalcoholic crude extract of Casearia sylvestris (HCE-CS) and contribution of pro-resolving mediators on mechanical hyperalgesia in a mouse model of chronic post-ischemia pain (CPIP). Methods and results Male Swiss mice were subjected to ischemia of the right hind paw (3 h), then reperfusion was allowed. At 10 min, 24 h or 48 h post-ischemia/reperfusion (I/R), different groups of animals were treated with HCE-CS (30 mg/Kg, orally [p.o]), selected agonists at the pro-resolving receptor ALX/FPR2 (natural molecules like resolvin D1 and lipoxin A4 or the synthetic compound BML-111; 0.1–1 µg/animal) or vehicle (saline, 10 mL/Kg, s.c.), in the absence or presence of the antagonist WRW4 (10 µg, s.c.). Mechanical hyperalgesia (paw withdrawal to von Frey filament) was asseseed together with histological and immunostainning analyses. In these settings, pro-resolving mediators reduced mechanical hyperalgesia and HCE-CS or BML-111 displayed anti-hyperalgesic effects which was markedly attenuated in animals treated with WRW4. ALX/FPR2 expression was raised in skeletal muscle or neutrophils after treatment with HCE-CS or BML-111. Conclusion These results reveal significant antihyperalgesic effect of HCE-CS on CPIP, mediated at least in part, by the pathway of resolution of inflammation centred on the axis modulated by ALX/FPR2.
Keywords: ALX/FPR2; Casearia sylvestris; Chronic post-ischemia pain; Inflammation; Salicaceae